Robots, Meaning, and Self-Determination - Milena Nikolova; Femke Cnossen; Nikolaev. Boris (Global Labor Organization (GLO), 2022)
We are the first to examine the impact of robotization on work meaningfulness and autonomy, competence, and relatedness, which are key for motivation and human flourishing at work. Using worker-level data from 13 industries in 20 European countries and OLS and instrumental variables estimations, we find that industry-level robotization harms all work quality aspects except competence. We also examine the moderating role of routine and cognitive tasks, skills and education, and age and gender. While we do not find evidence of moderation concerning work meaningfulness in any of our models, noteworthy differences emerge for autonomy. For instance, workers with repetitive and monotonous tasks drive the negative effects of robotization on autonomy, while social tasks and working with computers - a tool that provides worker independence - help workers derive autonomy and competence in industries and jobs that adopt robots. In addition, robotization increases the competence perceptions of men. Our results highlight that by deteriorating the opportunities to derive meaning and self-determination out of work, robotization will impact the present and the future of work above and beyond its consequences for employment and wages.
Keywords: J01; J30; J32; J81; I30; I31; M50; 330; work meaningfulness; self-determination theory; robotization; automation